An analysis of lexicogrammatical development in English textbooks in Turkey: A usage-based construction grammar approach - Gedik Tan Arda (ExELL (Explorations in English Language and Linguistics))
This article measures the syntactic development indices in grade 5-12 English textbooks in Turkey. Through a usage-based construction grammar approach, it argues that the textbooks show an inconsistent development in verb-argument constructions (VAC) and other usage-based indices. The study employs an automatic software tool that detects variations in these indices and runs a statistical analysis on a corpus compiled by the author. Statistically significant results demonstrate that textbooks lack lexicogrammatical variation. As such, learners who use these textbooks are likely to experience a limited array of VACs that are limited in lemma-construction combinations. Findings also indicate that learners may not be exposed to the conventional usage patterns and frequencies of VACs when compared against a reference corpus. These findings may have an influence on the learners’ generalization process, their low-proficiency level in English, and poor idiomatic uses of the language.